2018
DOI: 10.1007/s00259-018-4017-0
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET and high-resolution MRI co-registration for pre-surgical evaluation of patients with conventional MRI-negative refractory extra-temporal lobe epilepsy

Abstract: Pre-surgical evaluation by co-registration of F-FDG PET and HR-MRI could improve the identification of the epileptogenic onset zone (EOZ), and may further guide the surgical decision-making and improve the outcome of the refractory ETLE with normal conventional MRI; therefore, it should be recommended as a standard procedure for pre-surgical evaluation of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 11 publications
0
31
0
Order By: Relevance
“…In a subsequent study of 48 children, FDG-PET showed a clear advantage over MRI in detecting mild malformations of cortical development, which were missed in about 2/3 of the cases but detected by PET in 77% [23]. While some previous studies utilized suboptimal MRI, 1.5 T scanners, and/or lower resolution scans, a recent study used 3 T MRI with high-resolution images (1 mm 3 isotropic voxels) combined with co-registered FDG-PET in patients with non-localizing conventional MRI [24]. This approach detected a previously missed MRI lesion in 46% and confirmed a suspicious subtle lesion in 12% of the cases, thus supporting the importance of high-resolution MRI combined with PET imaging; as a result, the rate of detected focal abnormalities increased to 94% by PET/ MRI fusion as compared to 68% by PET alone.…”
Section: Fdg-pet In Children With Non-localizing Mri and Mild Cortical Developmental Malformationsmentioning
confidence: 99%
“…In a subsequent study of 48 children, FDG-PET showed a clear advantage over MRI in detecting mild malformations of cortical development, which were missed in about 2/3 of the cases but detected by PET in 77% [23]. While some previous studies utilized suboptimal MRI, 1.5 T scanners, and/or lower resolution scans, a recent study used 3 T MRI with high-resolution images (1 mm 3 isotropic voxels) combined with co-registered FDG-PET in patients with non-localizing conventional MRI [24]. This approach detected a previously missed MRI lesion in 46% and confirmed a suspicious subtle lesion in 12% of the cases, thus supporting the importance of high-resolution MRI combined with PET imaging; as a result, the rate of detected focal abnormalities increased to 94% by PET/ MRI fusion as compared to 68% by PET alone.…”
Section: Fdg-pet In Children With Non-localizing Mri and Mild Cortical Developmental Malformationsmentioning
confidence: 99%
“…Importantly, we found that the PET/MR allowed the detection of structural lesions in a high proportion of patients (24 %) in whom the MRI was initially considered negative, despite optimal examination including the co-registration with the PET. This multimodal approach has been previously reported as increasing the detection of FCDs [8][9][10][11] and considered as the reference method that should be recommended as a standard procedure for MRI negative ETLE [12]. However, according to our data, the PET/MR reaches a new step for the detection of such epileptogenic lesions compared to the reference imaging.…”
Section: Discussionmentioning
confidence: 66%
“…Surgical resection of the dysplastic cortex allows a favorable outcome [2][3], however FCDs can be di cult to identify by imaging even though using optimal MRI protocols [4][5][6][7]. 18 F-FDG PET has proved to be useful in negative MRI cases, and the additional value of the co-registration of PET and MRI has been demonstrated [8][9][10][11][12][13]. More recently, new hybrid PET/MR imaging has been developed, allowing simultaneous acquisition of brain metabolism images provided by 18 F-FDG PET and morphological/functional images by MRI under the same clinical conditions.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there are abundant available fusion software for fusing PET data with separately acquired MRI images satisfactorily (Ding et al, 2018). However, only hybrid PET/MRI system can provide the real time matched functional information representing disease states, which may undergo changes between the two separated imaging studies.…”
Section: Future Perspectivementioning
confidence: 99%
“…This combined dual-modalities (either sequential or simultaneous) could generate preferable soft tissue contrast of brain tissue, flexible acquisition parameters and minimized exposure to radiation (Musafargani et al, 2018). Fusion of PET and MRI images acquired at different time points from separated devices, has been performed routinely for brain imaging in a number of clinical centers (Zhu et al, 2017b; Ding et al, 2018). However, it must be pointed out that the physiological or mental state studied, respectively, by PET and MRI may differ in varying levels during the two separated imaging sessions.…”
Section: Introductionmentioning
confidence: 99%